Promotion of autonomy and self-regulation in higher education students - construction of a teaching and learning module insert in the project “interdisciplinary collaborative approaches to learning and teaching - Pereira,Cristina Maria (2021)
Abstract Introduction: In the context of participation in an ERASMUS + project “Interdisciplinary Collaborative Approaches to Learning and Teaching - INCOLLAB”, we propose to assay its innovative character in the field of pedagogy in higher education, highlighting the dimension of integrated learning of a foreign language and a content (Content and Language Integrated Learning)- CLIL) and collaboration between higher education teachers in planning learning modules and teaching materials based on a interdisciplinary design and intervention. Objective: Asses the learning of a foreign language through the project methodology. Methods: The methodology followed was that of an action-research, supported by a community of learning and practice. This modality allowed the professors of the universities involved in the project, from the areas of foreign language and different content areas (Psychology, Economics, Management ...), to share knowledge, skills and pedagogical perspectives, projecting this experience in the design and implementation of multidisciplinary modules in learning processes. Results: As an example of the work developed, we present the module “Autonomy Support: Through collaboration towards self-regulated learning strategies” which, based on the conceptual model of Deci & Ryan (1985, 2004), aims to constitute itself as an educational resource available, on an online platform, to professionals who can adapt it to other educational context. Having been conceived and applied experimentally to students of the 1st year of graduation, in the context of the Psychology of Development course unit, it can be adapted to any training area, mobilizing skills in the English language at level B1. Conclusion: The option for the theme of the module is based on the conception that the autonomy and self-regulation skills are transversal to academic success in higher education and future professional performance.